PENGARUH PEMBIAYAAN MODAL KERJA, INVESTASI DAN KONSUMSI TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Sappeami Sappeami; Anton Priyo Nugroho; Baharuddin Baharuddin (Indonesian Journal of Economics, Entrepreneurship, and Innovation, 2022)
Financing is the largest portion from the assets of Islamic banks because it is the main activity of banking system. Based on its use, financing is distributed through capital, investment, and consumption. The performance success of banking system is seen from its profitability. The objective of this research was to know the effects of financing of capital, investment, and consumption on the profitability of Islamic banks, proxied with ROA both in the long term and in the short term.This was a quantitative research with causal approach. This research population was all Islamic banks and Islamic enterprise units in Indonesia in January 2017 to November 2016. The data were analyzed using Error Correction Model (ECM). Based on the resulta of this research, the variable of capital financing in the long term has negative significant effect on the variable of ROA, while in the short term, this variable has no effect on the variable ROA. The variable of investment financing in the long term has positive significant on the variable of ROA, while in the short term, it does not have any effect on ROA. On the other hand, the consumption financing has no effect on ROA, neither in the long term nor in the short term. All variables simultaneously have significant effect on the profitability of Islamic banks in Indonesia in 2007-2016, both in the long term and in the short term